2018
DOI: 10.21873/invivo.11440
|View full text |Cite
|
Sign up to set email alerts
|

Maslinic Acid Enhances Immune Responses in Leukemic Mice Through Macrophage Phagocytosis and Natural Killer Cell Activities In Vivo

Abstract: Background/Aim: Maslinic acid (MA), a pentacyclic triterpene extracted from wax-like coatings of olives, has been shown to reduce cancer cell number through induction of autophagy and apoptosis in many human cancer cells including human leukemia HL-60 cells. In the present study, we investigated whether or not MA affects immune responses in a leukemia mouse model. Materials and Methods: WEHI-3 cells were intraperitonealIy (i.p.) injected into normal BALB/c mice to develop leukemia. Mice were then treated by i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
7
1
1
Order By: Relevance
“…↓IL-6, ↓TNF-α, ↑IL-10, [ 42 ] 5-week-old male BALB/c nude mice HCT116 xenograft model 10 mg/kg and 30 mg/kg day-1 Orally 17 days Suppressed the tumorigenesis, ↓p-mTOR, ↓p-4EBP1, ↓p70S6K,↑p- AMPK. [ 42 ] Leukemia 5-week-old male BALB/c mice WEHI-3 xenograft model 0, 8, 16, 32 mg/Kg Intraperitoneal injection 2 weeks Increase immune responses: enhanced macrophage phagocytosis and NK cell activities [ 80 ] Pancreatic cancer er 4–5 week-old athymic nu/nu male mice Panc-28 xenograft model 10, 50 mg/kg MA every 2 day Subcutaneous injected 36 days Suppressed pancreatic tumor growth, induced tumor apoptosis, and inhibited NF-B-regulated anti-apoptotic gene expression, such as Survivin and Bcl-xl. [ 112 ] Gallbladder cancer 6-week-old athymic nu/nu male mice EH-GB2 xenograft model 30 mg/kg MA every 2 days+GEM Subcutaneously injected 30 days Inhibitory tumor volume, and decreased NF-κB-regulated gene products expression.…”
Section: Anticancer Properties Of Maslinic Acidmentioning
confidence: 99%
“…↓IL-6, ↓TNF-α, ↑IL-10, [ 42 ] 5-week-old male BALB/c nude mice HCT116 xenograft model 10 mg/kg and 30 mg/kg day-1 Orally 17 days Suppressed the tumorigenesis, ↓p-mTOR, ↓p-4EBP1, ↓p70S6K,↑p- AMPK. [ 42 ] Leukemia 5-week-old male BALB/c mice WEHI-3 xenograft model 0, 8, 16, 32 mg/Kg Intraperitoneal injection 2 weeks Increase immune responses: enhanced macrophage phagocytosis and NK cell activities [ 80 ] Pancreatic cancer er 4–5 week-old athymic nu/nu male mice Panc-28 xenograft model 10, 50 mg/kg MA every 2 day Subcutaneous injected 36 days Suppressed pancreatic tumor growth, induced tumor apoptosis, and inhibited NF-B-regulated anti-apoptotic gene expression, such as Survivin and Bcl-xl. [ 112 ] Gallbladder cancer 6-week-old athymic nu/nu male mice EH-GB2 xenograft model 30 mg/kg MA every 2 days+GEM Subcutaneously injected 30 days Inhibitory tumor volume, and decreased NF-κB-regulated gene products expression.…”
Section: Anticancer Properties Of Maslinic Acidmentioning
confidence: 99%
“…α-Phellandrene (α-PA) is a monoterpene compound, which is found in essential oils or extracts from natural plants, particularly in spices and herbs such as pine (1), ginger (2), dill (3) and peppermint (4). Previous studies have shown that α-PA has antidepressant (5), anti-inflammatory (6), immunoregulatory (7) and anticancer (8) effects. Our previous research demonstrated that α-PA can induce cell death by decreasing ATP levels (9) and trigger autophagy by affecting AKT/LC3II/mTOR signaling in human liver cancer cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to inhibit angiogenesis (Thakor et al, 2017 ) and cell migration and invasion in several cancers (Wei et al, 2019 ; Zhang et al, 2021 ). Moreover, MA can modulate the inflammatory response and potentiate the immune system action against cancer cells (Sánchez-Quesada et al, 2015 ; Lai et al, 2019 ). Sánchez-Quesada et al reported that MA promoted the in vitro production of pro-inflammatory and macrophage recruitment-related cytokines in macrophages and that it favored their differentiation to M1 state, which is the phenotype involved in the immune defense against cancer cells (Sánchez-Quesada et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%